POLA KOMUNIKASI DALAM PEMBERIAN SANKSI ADAT TERHADAP PELAKU KAWIN LARI - Yanto Yanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2019)
In order to achieve a common goal in a society, sometimes the exchange of messages can be biased, therefore it is important how the communication patterns in giving a support to the elopement, so that problems do not arise in the future. Therefore, the writer wants to see and know the communication patterns that take place in the granting of sanctions to the elopement in BatuEjung village. This type of research is qualitative research, data sources in this study were taken from primary data and secondary data, data collection techniques were carried out by interview observation and documentation. Analysis techniques by data reduction, data presentation, then drawing conclusions / verification. The results of studies of various types of communication patterns, ranging from primary communication patterns, secondary communication patterns, linear communication patterns and circular communication patterns, the most suitable and approaching in sanctioning elopement actors are primary communication patterns because they include which elements in the pattern This is divided into two symbols, verbal symbols and nonverbal symbols. In verbal or language symbols, it can be seen how dialogue patterns that occur between indigenous people and the host convey the problem directly, in a nonverbal pattern the process of communicating thoughts by the communicator to the communicant using a symbol, known as "tepunjung" both yellow arbor and white arbor, and payment of a fine in cash. Keywords: communication patterns, customs, elopement